2015
DOI: 10.1089/vim.2014.0129
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus andHuman herpes virus 6Type A DNA Enhance IL-17 Production in Mice

Abstract: Several studies have shown a potential association between the Herpesviridae members, the Epstein-Barr virus (EBV) and Human herpes virus 6 (HHV-6), and an increased risk of autoimmune disease development. Because of the ability of these viruses to cause recurrent infections, various viral antigens, including viral DNA, are consistently shed. These antigens may then play a role in triggering autoimmune processes or contributing to autoimmune mechanisms. Therefore, this study examined whether the DNA of EBV or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…In contrast, IL-17 is associated with the pathology in 2009 pandemic influenza A (H1N1)-induced acute lung injury 140 . Additionally, IL-17 levels are associated with the exacerbated disease pathology induced following viral infections such as hepatitis 141, 142 , vaccinia virus 143, 144 , RSV 145147 , HSV 148, 149 , and EBV 150, 151 . During viral infections (such as hepatitis), IL-17 can either potentiate early neutrophil infiltration at the site of infection 152 or inhibit NK cell-mediated host immune response (for example, vaccinia virus infection) 153 .…”
Section: Role Of Il-17 In Viral Infectionmentioning
confidence: 99%
“…In contrast, IL-17 is associated with the pathology in 2009 pandemic influenza A (H1N1)-induced acute lung injury 140 . Additionally, IL-17 levels are associated with the exacerbated disease pathology induced following viral infections such as hepatitis 141, 142 , vaccinia virus 143, 144 , RSV 145147 , HSV 148, 149 , and EBV 150, 151 . During viral infections (such as hepatitis), IL-17 can either potentiate early neutrophil infiltration at the site of infection 152 or inhibit NK cell-mediated host immune response (for example, vaccinia virus infection) 153 .…”
Section: Role Of Il-17 In Viral Infectionmentioning
confidence: 99%
“…, Rahal et al . ); thus, EBV may be associated with not only carcinogenesis but also pathogenesis in local inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…EBV has also been implicated in malignancies such as gastric cancer, Hodgkin disease and T-cell lymphoma (Abe et al 2015, Chua et al 2015, Vockerodt et al 2015. EBV infection induces expression of proinflammatory cytokines such as tumour necrosis factor-a, interleukin (IL)-1b, IL-8, IL-10, IL-12, and IL-17 (Morris et al 2008, Murakami et al 2014, Rahal et al 2015; thus, EBV may be associated with not only carcinogenesis but also pathogenesis in local inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that EBV DNA enhances the production of the proinflammatory cytokine IL-17A as well as IL-23, tumor necrosis factor (TNF-␣), and IFN-␥ when injected into mice (25,65). IL-17A plays a role in host defenses against bacterial and fungal infections (26).…”
mentioning
confidence: 99%